Male pseudohermaphroditism due to 5-alpha reductase type-2 deficiency in a 20-month old boy - Ida Bagus Andhita; Wayan Bikin Suryawan (Indonesian Pediatric Society, 2006)
5-alpha-reductase (5-ARD) type 2 deficiencyis an autosomal sex-linked disorder, resulting inthe inability to convert testosterone to the morephysiological active dihydrotestosterone (DHT).DHT is the most potent androgen, bound selec-tively to the androgen receptors in genital skin andfibroblasts, making its action necessary for the de-velopment of normal male genital anatomy. SinceDHT is required for normal masculinizaton of theexternal genitalia in utero, genetic males with 5-ARD are usually born with ambiguous genitalia(male pseudohermaphroditism). The hallmarkof 5-ARD is elevated ratio of serum testosteroneto DHT. In healthy prepubertal children, thebaseline testosterone-to-DHT ratio is 1:2. Thispaper reports a 20-month old patient with malepseudohermaphroditism due to 5-alpha reductasetype-2 deficiency.